2007
DOI: 10.1177/1069072707301211
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Assessment of Women's Career Choices: The Career Aspiration Scale

Abstract: The results of five studies illustrated sound psychometric properties of the CAS when used with adolescent, college, and postcollege samples comprised predominantly of White women. The final eight-item measure demonstrated strong testretest reliability over a 2-week period and evidenced moderate internal consistency. Convergent validity was supported by correlations with measures of career decision self-efficacy, multiple role self-efficacy, occupational self-efficacy, attitudes toward women's roles, instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 20 publications
3
109
1
5
Order By: Relevance
“…The career aspiration scale (CAS; Gray & O'Brien, 2007) consists of two subscales: the Leadership and Achievement Aspiration Scale (eight items, e.g., 'I hope to become a leader in my career field') and the Educational Aspiration Scale (two items, e.g., 'I think I would like to pursue graduate training in my occupational area of interest'). Although the measure of career aspiration developed by Gray and O'Brien (2007) is comprised of two dimensions, the CAS score was computed as a single index, dropping four items of the factor Leadership and Achievement Aspirations because of low reliability and the confirmatory factor analysis (CFA) results indicating a single factor and high cross-loadings for the current sample. This decision is in line with the previous research that has reported very low reliabilities of the Educational Aspiration Scale, and it was suggested that two items of the Leadership and Achievement Aspiration Scale be dropped (e.g., Study 3 in Gray & O'Brien, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The career aspiration scale (CAS; Gray & O'Brien, 2007) consists of two subscales: the Leadership and Achievement Aspiration Scale (eight items, e.g., 'I hope to become a leader in my career field') and the Educational Aspiration Scale (two items, e.g., 'I think I would like to pursue graduate training in my occupational area of interest'). Although the measure of career aspiration developed by Gray and O'Brien (2007) is comprised of two dimensions, the CAS score was computed as a single index, dropping four items of the factor Leadership and Achievement Aspirations because of low reliability and the confirmatory factor analysis (CFA) results indicating a single factor and high cross-loadings for the current sample. This decision is in line with the previous research that has reported very low reliabilities of the Educational Aspiration Scale, and it was suggested that two items of the Leadership and Achievement Aspiration Scale be dropped (e.g., Study 3 in Gray & O'Brien, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Although the measure of career aspiration developed by Gray and O'Brien (2007) is comprised of two dimensions, the CAS score was computed as a single index, dropping four items of the factor Leadership and Achievement Aspirations because of low reliability and the confirmatory factor analysis (CFA) results indicating a single factor and high cross-loadings for the current sample. This decision is in line with the previous research that has reported very low reliabilities of the Educational Aspiration Scale, and it was suggested that two items of the Leadership and Achievement Aspiration Scale be dropped (e.g., Study 3 in Gray & O'Brien, 2007). The reliability for the total CAS score of the remaining items was .73.…”
Section: Methodsmentioning
confidence: 99%
“…It was designed in a way to measure both intentions and behavior because behavior is considered to be a more objective indicator than intentions only (Tharenou and Terry, 1998). With regards to the former, the "leadership and achievement scale" developed by Gray and O'Brien (2007) was employed. Further, also three more items were introduced to fulfill their request to enlarge the scale.…”
Section: Methodsmentioning
confidence: 99%
“…Good (1959, cited in Nanda, 2008 defines aspiration as the degree to which a person sets a realistic goal, which is associated with preexisting mental and environmental attributes. Aspiration can also be desires, hopes and ideals related to a cause (Gray & O'Brien, 2007). For example, leadership aspirations mean the desires, hopes and ideals related to leadership in the chosen career field.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the leadership aspirations of women are the desires, hopes and ideals of women to be leaders with all the personal and social complexities that surround them, which include getting a promotion, leading and training others, and becoming known as a leader in a particular field (Gray & O'Brien, 2007). Meanwhile, perceptions regarding leadership aspirations of women is the process of acquisition, interpretation, selection and arrangement of sensory information regarding leadership aspirations held by women (Takwin, 2009).…”
Section: Introductionmentioning
confidence: 99%